Identification of new biophysical markers for pathological ventricular remodelling in tachycardia‐induced dilated cardiomyopathy. Issue 9 (19th June 2018) - Benitez‐Amaro, Aleyda; Samouillan, Valerie; Jorge, Esther; Dandurand, Jany; Nasarre, Laura; de Gonzalo‐Calvo, David; Bornachea, Olga; Amoros‐Figueras, Gerard; Lacabanne, Colette; Vilades, David; Leta, Ruben; Carreras, Francesc; et al.
Abstract: Our aim was to identify biophysical biomarkers of ventricular remodelling in tachycardia‐induced dilated cardiomyopathy (DCM). Our study includes healthy controls (N = 7) and DCM pigs (N = 10). Molecular analysis showed global myocardial metabolic abnormalities, some of them related to myocardial hibernation in failing hearts, supporting the translationality of our model to study cardiac remodelling in dilated cardiomyopathy. Histological analysis showed unorganized and agglomerated collagen accumulation in the dilated ventricles and a higher percentage of fibrosis in the right (RV) than in the left (LV) ventricle ( P = .016). The Fourier Transform Infrared Spectroscopy (FTIR) 1st and 2nd indicators, which are markers of the myofiber/collagen ratio, were reduced in dilated hearts, with the 1st indicator reduced by 45% and 53% in the RV and LV, respectively, and the 2nd indicator reduced by 25% in the RV. The 3rd FTIR indicator, a marker of the carbohydrate/lipid ratio, was up‐regulated in the right and left dilated ventricles but to a greater extent in the RV (2.60‐fold vs 1.61‐fold, P = .049). Differential scanning calorimetry (DSC) showed a depression of the freezable water melting point in DCM ventricles – indicating structural changes in the tissue architecture – and lower protein stability. Our results suggest that the 1st, 2nd and 3rd FTIR indicators are useful markers of cardiac remodelling. Moreover, the 2nd and 3rd FITR indicators, which are altered to a greater extent in the right ventricle, are associated with greater fibrosis.